Building Information Modelling analysis of proposed Skycourt Apartment Prototype and Conventional affordable apartment in Malaysia - Mohammad Ezzad Abu Bakar , Roshida Abdul Majid , Mohd Azwarie Mat Dzahir (International Journal of Advanced Science and Technology, 2020)
This paper proposes ‘Skycourt Apartment’ as a solution for more socially sustainable high-riseresidential and considerably more cost-effective in comparison with Malaysian conventional affordableapartments. The provision of skycourt is proven to be a socially sustainable and environmentally viableoption for high-rise living, as numerous previous researchers have shown the potential for this greencommunal space. The principal contribution of this paper includes the cost feasibility validation ofskycourt apartment prototype to be applied specifically in Malaysia’s affordable apartment typology. Thevalidation process is carried out by having a comparison of Bill of Quantity between the proposedprototypes of skycourt apartment with a selected conventional affordable apartment in Johor Bahru asthe base comparator. Both buildings are modelled in Revit before cost simulation is employed on each ofthe Building Information Model as the tool to generate the Bill of Quantity. The result shows that theproposed skycourt prototype design is feasible to be applied in affordable apartment typology inMalaysia. The prototype design is potentially useful for application in the Malaysian affordable housingscheme and thus could benefit economically to the stakeholders involved